NADPH oxidase 4 mediates the protective effects of physical activity against obesity-induced vascular dysfunction. Issue 10 (4th December 2019) - Brendel, Heike; Shahid, Amna; Hofmann, Anja; Mittag, Jennifer; Bornstein, Stefan R; Morawietz, Henning; Brunssen, Coy
Abstract: Aims: Physical activity is one of the most potent strategies to prevent endothelial dysfunction. Recent evidence suggests vaso-protective properties of hydrogen peroxide (H2 O2 ) produced by main endothelial NADPH oxidase isoform 4 ( Nox4 ) in the vasculature. Therefore, we hypothesized that Nox4 connects physical activity with vaso-protective effects. Methods and results: Analysis of the endothelial function using Mulvany Myograph showed endothelial dysfunction in wild-type (WT) as well as in C57BL/6J/ Nox4 −/− ( Nox4 −/− ) mice after 20 weeks on high-fat diet (HFD). Access to running wheels during the HFD prevented endothelial dysfunction in WT but not in Nox4 −/− mice. Mechanistically, exercise led to an increased H2 O2 release in the aorta of WT mice with increased phosphorylation of eNOS pathway member AKT serine/threonine kinase 1 (AKT1). Both H2 O2 release and phosphorylation of AKT1 were diminished in aortas of Nox4 −/− mice. Deletion of Nox4 also resulted in lower intracellular calcium release proven by reduced phenylephrine-mediated contraction, whilst potassium-induced contraction was not affected. H2 O2 scavenger catalase reduced phenylephrine-induced contraction in WT mice. Supplementing H2 O2 increased phenylephrine-induced contraction in Nox4 −/− mice. Exercise-induced peroxisome proliferative-activated receptor gamma, coactivator 1 alpha ( Ppargc1a ), as key regulator of mitochondria biogenesis in WT but not Nox4 −/− mice. Furthermore, exercise-induced citrate synthase activity and mitochondria mass were reduced in the absence of Nox4 . Thus, Nox4 −/− mice became less active and ran less compared with WT mice. Conclusions: Nox4 derived H2 O2 plays a key role in exercise-induced adaptations of eNOS and Ppargc1a pathway and intracellular calcium release. Hence, loss of Nox4 diminished physical activity performance and vascular protective effects of exercise. Graphical Abstract: